Analysis of the Application of the Six Sigma Method in Quality Control of the Mirror Packaging Process: A Case Study of UMKM Moca More Store - Maharani, Liana; Sari, Rini Mulyani (International Journal of Education, Management, and Technology, 2025)
This study evaluates and enhances the quality control process at Moca More Store, a micro, small, and medium enterprise (MSME), through the application of the Six Sigma methodology. Using data from January to September 2024, quality issues were analyzed via Defects Per Million Opportunities (DPMO), sigma level calculation, control charts, Pareto diagrams, and fishbone diagrams. Results indicate considerable process variability, with DPMO values ranging from a peak of 8,833 in July to a low of 5,563 in April, and a maximum sigma level of only 2.77. Inadequate packaging accounted for 78.83% of defects, making it the primary improvement target. Root cause analysis identified human factors, methods, machinery, and raw materials as major contributors to the problem. The improvement and control phases implemented standard operating procedures and real-time monitoring tools to reduce defects and stabilize processes. The study concludes that Six Sigma can effectively pinpoint and address critical quality issues in MSMEs, but long-term improvement requires embedding a quality-oriented culture, maintaining systematic control mechanisms, and integrating continuous feedback.